2016
DOI: 10.1093/ejcts/ezw056
|View full text |Cite
|
Sign up to set email alerts
|

Expectations and limitations after bilateral pulmonary artery banding

Abstract: Bil-PAB could be applied to a wide variety of complex diseases. Our mortality rates with bil-PAB improved significantly post-2010. Good indications for bil-PAB were shock and situations where it was unclear whether the physiology was single ventricle or biventricular. Body weight gain was difficult to predict, but patients weighing less than 2.5 kg could be expected to gain body weight after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 15 publications
1
19
0
Order By: Relevance
“…The appropriate timing of second stage surgery has been a dilemma as the weight gain post bilateral PA banding was found to have individual variations [1]. Although commonly done at 3 to 6 months post bilateral PA band, the surgery was significantly delayed in our case due to concomitant and ongoing infection pertaining to the immunodeficiency [3].…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…The appropriate timing of second stage surgery has been a dilemma as the weight gain post bilateral PA banding was found to have individual variations [1]. Although commonly done at 3 to 6 months post bilateral PA band, the surgery was significantly delayed in our case due to concomitant and ongoing infection pertaining to the immunodeficiency [3].…”
Section: Discussionmentioning
confidence: 82%
“…Bilateral PA banding as a staged palliation is predominantly used for single ventricle lesions. However, recent reports have shown that it has become an established palliation for biventricular lesions, especially in truncus arteriosus defect [1]. In view of increased risk of perioperative mortality and reoperation for single-stage repair of complex cardiac lesions in neonates with low birth weight, reports have demonstrated the benefit of bilateral PA band to allow weight gain and maturation of vital organs [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12,13 The higher proportion of Glenn operations among the benchmark procedures in JCVSD-Congenital compared to ECHSA-CHSD may reflect the advanced experiences in Japan regarding functionally univentricular palliation. 14 Surprisingly, the proportion of Fontan completion is lower in JCVSD-Congenital compared to ECHSA-CHSD.…”
Section: Discussionmentioning
confidence: 94%